How does geographical branding improve the efficiency of the apple supply chain? - Noori, Siavash; Niknami, Mehrdad; Sabouri, Mohammad Sadegh; Rafiee, Hamed (Frontiers in Sustainable Food Systems, 2024)
Brands are among the most valuable assets of agricultural businesses. Geographical branding can play a fundamental role in national and international markets by creating a competitive identity. On the other hand, orchard owners in a certain geographical region can understand the status of a product's supply chain. Nonetheless, few studies have focused on how branding can influence the status of a product's supply chain. Thus, the present study aimed to analyze the effect of geographical branding on improving the apple supply chain. The research is an applied study in terms of the goal, conducted by the survey methodology. Data were collected by distributing 360 questionnaires among apple orchard owners in Damavand County sampled by simple randomization. Cochran's formula estimated the sample size. The research instrument was a research-made questionnaire. Data were analyzed by structural equation modeling. According to the results, special brand value, brand loyalty, brand image, brand attitude, brand experience, brand purchasing intention, and brand identity were the components found to improve the efficiency of the Apple supply chain significantly.